Venous hemangioma of the anterior mediastinum. (22nd December 2014) - Yilmaz, Adnan; Kavas, Murat; Ersev, Ayşe; Ekinci, Gulbanu Horzum; Haciomeroglu, Osman; Atinkaya, Cansel; Akkaya, Esen
Abstract: Mediastinal hemangiomas are rare tumors, with an incidence of 0.5% or less. We herein present a case of venous hemangioma in the anterior mediastinum. A 61‐year‐old man was admitted to our hospital complaining of dyspnea. Computed tomography scan of the thorax showed a 2.5 × 3.2 × 2 cm mass in the anterior mediastinum. Using a median sternotomy approach, the tumor was completely removed. Pathological examination confirmed a venous hemangioma.